Placenta Previa Complicated with Endometriosis: Contemporary Clinical Management, Molecular Mechanisms, and Future Research Opportunities - Matsuzaki, Shinya; Nagase, Yoshikazu; Ueda, Yutaka; Kakuda, Mamoru; Maeda, Michihide; Matsuzaki, Satoko; Kamiura, Shoji (Biomedicines, 2021)
Endometriosis is a common gynecological disease characterized by chronic inflammation, with an estimated prevalence of approximately 5–15% in reproductive-aged women. This study aimed to assess the relationship between placenta previa (PP) and endometriosis. We performed a systematic review of the literature until 30 June 2021, and 24 studies met the inclusion criteria. Using an adjusted pooled analysis, we found that women with endometriosis had a significantly increased rate of PP (adjusted odds ratio (OR) 3.17, 95% confidence interval (CI) 2.58–3.89) compared to those without endometriosis. In an unadjusted analysis, severe endometriosis was associated with an increased prevalence of PP (OR 11.86, 95% CI 4.32–32.57), whereas non-severe endometriosis was not (OR 2.16, 95% CI 0.95–4.89). Notably, one study showed that PP with endometriosis was associated with increased intraoperative bleeding (1.515 mL versus 870 mL, p < 0.01) compared to those without endometriosis. Unfortunately, no studies assessed the molecular mechanisms underlying PP in patients with endometriosis. Our findings suggest that there is a strong association between endometriosis and a higher incidence of PP, as well as poor surgical outcomes during cesarean delivery. Therefore, the development of novel therapeutic agents or methods is warranted to prevent PP in women with endometriosis.